IPastoral. (4th April 2013) - Morris, Mark
Abstract: Architectural theorist and educatorMark Morris parallels the 18th‐century enthusiasm for the Claude glass, a black mirror that framed and filtered views into painterly landscapes, with the current infatuation for a similarly small shiny black device with a capacity for taking picturesque images.